The handbook of program management: how to facilitate project success with optimal program management, second edition - Brown, James T. 1960- (McGraw-Hill, 2014)
This go-to guide supplies you with the insight and tools you need to establish processes that ensure the success of your project managers--and increase the profitability of your products and services. Fully updated and heavily revised, this new edition helps you incorporate new technologies and people into your processes while delivering improved products and services that continually outpace your competition. In addition to the classic chapters, this updated edition is packed with brand new material covering: change management; interfaces; how bad projects are stopped or postponed; how consultants and subcontractors should be used; program performance analysis; and the role of governance. The author takes you on the entire journey, from strategically creating a program culture, to building effective relationships, and to analyzing ways of accomplishing your program objectives. --
Includes bibliographical references. - Print version record
Keywords: Project management -- Handbooks, manuals, etc; Gestion de projet; Guides, manuels, etc; BUSINESS & ECONOMICS; Management; Project management; handbooks; Handbooks and manuals; Guides et manuels; Handbook